Benign recurrent intrahepatic cholestasis: studies of bilirubin kinetics, bile acids, and cholangiography. Issue 2 (February 1980) - Summerfield, J A; Scott, J; Berman, M; Ghent, C; Bloomer, J R; Berk, P D; Sherlock, S
Abstract : Three patients with benign recurrent intrahepatic cholestasis are described. They had had between five and 16 attacks of cholestasis. Between attacks the liver function tests, including serum bile acids, were normal. Serial serum bilirubin and bile acid estimations during the cholestasis in one patient revealed a consistent discrepancy between the serum bilirubin and bile acid concentrations during three consecutive attacks. In the other two patients the serum concentrations of bile acids and bilirubin varied in parallel. Analysis of the individual serum bile acids did not reveal high concentrations of any 'toxic' bile acid. In one patient, plasma bromsulphthalein (BSP) curves were obtained during both remission and cholestatic periods. The 45 minute retention was slightly increased (10.8%) during remission. During the cholestasis, the 45 minute retention (25%) and the fractional extraction coefficient (Ke=0.069 min-1) were markedly abnormal. The hepatic clearance of unconjugated radiobilirubin was normal at all times in this patient, although during cholestasis, conjugated bilirubin reflexed from the liver to the plasma and was then cleared slowly with a half life of approximately 12 hours. Treatment with corticosteroids, cholestyramine, and phenobarbitone was unsatisfactory.